The impact of work environment and workload on job satisfaction: An empirical study of teachers in Chinese private higher educational institutes - Li, Wang; Khatibi, Ali; Tham, Jacqueline (Edelweiss Applied Science and Technology, 2025)
This research endeavors to examine how the working conditions and professional demands influence the occupational contentment of educators within China’s private tertiary education sector. By distributing structured questionnaires to 300 academic administrators across nine universities in Anhui Province and utilizing AMOS 23.0 software for Structural Equation Modeling (SEM) analysis, this research examines the relationships among these three aspects. The results indicate that an improved workplace atmosphere positively contributes to job satisfaction, while excessive job responsibilities have a notable adverse effect. The study recommends that universities should optimize their work environments and reasonably control teachers’ workloads to enhance overall job satisfaction.